Data for: Sedimentary ancient DNA and pollen reveal the composition of plant organic matter in Late Quaternary permafrost sediments of the Buor Khaya Peninsula (north-eastern Siberia) ... - Zimmermann, Heike; Raschke, Elena; Epp, Laura S.; Stoof-Leichsenring, Kathleen R.; Schwamborn, Georg; Schirrmeister, Lutz; Overduin, Pier Paul; Herzschuh, Ulrike (Dryad, 2020)
Organic matter deposited in ancient, ice-rich permafrost sediments is vulnerable to climate change and may contribute to the future release of greenhouse gases; it is thus important to get a better characterization of the plant organic matter within such sediments. From a Late Quaternary permafrost sediment core from the Buor Khaya Peninsula, we analysed plant-derived sedimentary ancient DNA (sedaDNA) to identify the taxonomic composition of plant organic matter, and undertook palynological analysis to assess the environmental conditions during deposition. Using sedaDNA, we identified 154 taxa and from pollen and non-pollen palynomorphs we identified 83 taxa. In the deposits dated between 54 and 51 kyr BP, sedaDNA records a diverse low-centred polygon plant community including recurring aquatic pond vegetation while from the pollen record we infer terrestrial open-land vegetation with relatively dry environmental conditions at a regional scale. A fluctuating dominance of either terrestrial or swamp and ... : From a Late Quaternary permafrost sediment core (BK-8) from the Buor Khaya Peninsula, we analysed plant-derived sedimentary ancient DNA (sedaDNA) to identify the taxonomic composition of plant organic matter. Total DNA was extracted from 54 samples which were processed in 5 batches of up to 11 samples and one negative control. The PCR reactions were performed with the trnL g and h primers (Taberlet et al., 2007). Both primers were modified on the 5′end by unique 8 bp tags which varied from each other in at least five base pairs to distinguish samples after sequencing (Binladen et al., 2007) and were additionally elongated by NNN tagging to improve cluster detection on the sequencing platform (De Barba etal., 2014). For each sample, we pooled two positive PCR products for sequencing, under the condition that the associated NTCs and extraction blank were negative. The two pooled PCR products were purified using the MinElute PCRPurification Kit and subsequently the samples were pooled in equal concentrations. ...